ACADEMICIAN PROFESSOR DR. EMIL BURZO ON HIS 80TH ANNIVERSARY - POP, Aurel (Studia Universitatis Babeș-Bolyai Physica, 2015)
Professor Emil Burzo was born in 1935, August 30, in Moreni, county Dâmboviţa. He graduated Faculty of Physics from Babeș-Bolyai University Cluj-Napoca in 1959 and in 1958 Faculty of Mechanics from Technical University Cluj-Napoca. Prof. Emil Burzo earned his PhD in Physics at University of Timisoara in 1972, under the guidance of professor A.Cişman and professor P.Lamoth. Career: engineer at Carbochim plants in Cluj-Napoca (1958-1963); associate engineer and lecturer at Babes-Bolyai University, Cluj-Napoca (1964-1969); Institute of Physics Bucharest (researcher (1969), Senior Researcher III (1971); Senior Researcher II (1978); Senior researcher (1984); Head of Laboratory (1974-1976); Professor at University Babes-Bolyai University (1990 - present), and dean of the Faculty of Physics (1992-2000). Prof. Emil Burzo was Director of the Center of Excellence “Solid State Physics” (certified by MET) and Multi-User Research Base, and PhD superviser in specialities Solid State Physics and Materials Science. As PhD superviser prof. Emil Burzo guided around 40 Ph.D students, including 10 under the co-guardianship with the Universities of Grenoble, Strasbourg and Paris.